Debate on the Indonesian Question in the Security Council. At table from left: Sastroamidjojo, Ingles, Pillai, Gromyko and Cadogan
Debate on the Indonesian Question in the Security Council. At table from left: Sastroamidjojo, Ingles, Pillai, Gromyko and Cadogan.